Body language sales secrets : how to read prospects and decode subconscious signals to get results and close the deal - McCormick, Jim (James Maxwell); Karinch, Maryann (Business professional collection, 2018)
Helping salespeople at any level build rapport through active listening, invitational body language, and mirroring, this book reveals how your own body language can reinforce the perception of competence, relevance, and truth --